SISTEM INFORMASI GEOGRAFIS PEMETAAN AREA PERSAWAHAN DESA GANTUNG KABUPATEN BELITUNG TIMUR - Jepri Ardianto; Uning Lestari; Joko Triyono (Jurnal SCRIPT, 2016)
The information systemis aninformationtechnologythat is currentlygrowingso rapidly. The information can help easily, quickly, safely and effectively, clearly it is helpful to anyone who use it. Including Geographic Information Systems(GIS), which became one of theinformation storagemedia, primarilyforinformation related tospatial data. Google Maps API is one of the popular GIS technologies. With this technology can be made a map with a specific purpose such as making rice field area map. This technology will be applied in the system, so it can help Agriculture Department of Belitung Timur Regencyin monitoring the utilization of agricultural landsas well as agricultural potential in Gantung village of Belitung Timur Regency presented in map. The success of this systemsis to facilitate the implementation of Agriculture Department to monitor the utilization of agricultural land, asses and manage spatial data and attributes such as farmers' groups, member of farmer groups, plants and harvestas well as the agricultural potential.